Determinants of parental involvement in early literacy development: a scoping review - Solichah, Novia; Fardana, Nur Ainy; Samian, Samian (Intelektual Pustaka Media Utama, 2025)
Parental involvement plays a pivotal role in fostering early literacy skills. Understanding the factors influencing parental involvement is essential for promoting effective intervention in childhood. This study aims to identify and explore the determinants of parental involvement in early literacy development. The scoping review adheres to PRISMA guidelines from eight electronic databases: SAGE, Research Gate, Semantic Scholar, Google Scholar, Science Direct, Taylor and Francis, Scopus, and Springer. The criteria include research on parental involvement and early literacy, handling children aged 0-6 years and parents, and publishing original research articles and literature reviews. The search yielded 13 relevant studies. The analysis results show the following determinants of parental involvement in early literacy development: internal factors (i.e., parent depression, parent fidelity, parental genetics, parent's perspective, parent's support, parental positive motivation and belief, parental estimation, and parent expectation) and external factors (i.e., socioeconomic status, parents' education, parental literacy experience, family risk home literacy environment, and emergent literacy skills). The study results aim to inform targeted interventions to enhance parental involvement in early literacy across diverse contexts.